Pengaruh Inflasi dan Suku Bunga terhadap Harga Saham Perusahaan Perbankan - Eva; Nurmin; Haekal Yunus, Muh; Sahabuddin, Dewi Hardiyanti; Magnus A.M; Pratama, Rahmat Putra (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2026)
The objectives of this study were: 1) to determine the effect of inflation and interest rates on stock prices in banking companies, 2) to determine the effect of interest rates on stock prices in banking companies, and 3) to determine the effect of interest rates on stock prices in banking companies. This study was conducted by collecting secondary data in the form of financial reports of banking companies, inflation data, and data on Bank Indonesia interest rates. The results of the study indicate that: 1) inflation does not significantly affect stock prices in banking companies. This is evidenced by the results of partial tests obtained a t-value of up to 0.559 < the t-table value of 1.968 and a significance of 0.577 > 0.05, 2) interest rates significantly affect stock prices in banking companies. This is evidenced by the results of partial tests obtained a t-value of 0.-1.997 < the t-table value of 1.968 and a significance of 0.047 > 0.05, and 3) inflation and interest rates do not significantly affect stock prices in banking companies. This is proven by a simultaneous test where the calculated f value is 2.013 which is greater than the f table value which is 3.04 and significant at 0.136 which is smaller than 0.05 with a percentage influence of 1.8%.